ANALISIS KEPUTUSAN NASABAH MENGGUNAKAN MANDIRI AGEN DI DESA NANGA DEDAI KECAMATAN DEDAI KABUPATEN SINTANG - Yasri, Fadhila; Marganingsih, Anna; Astikawati, Yunita (STKIP Persada Khatulistiwa Sintang, 2025)
Banking Agents to provide banking services that are difficult to reach by people in rural areas which causes customers to spend high costs to reach these services. The purpose of this study was to analyze the factors that influence customer decisions in using Mandiri Agent services in Nanga Dedai Village, Dedai District, Sintang Regency. Mandiri Agent services make it easy for people who live in remote areas to access banking services without having to go to a branch office. This research uses a qualitative approach. Data collection techniques using interviews. The results explain that customer decisions are influenced by several main factors, namely ease of access, trust in services, and the level of customer understanding of the products offered. Social and economic factors, such as lower transaction costs and strategic agent locations, also play an important role in customers' decisions to use Mandiri Agen. Based on these findings, it can be concluded that the Mandiri Agen service is very helpful to the community in Nanga Dedai Village in fulfilling their banking needs, and an increase in understanding and service quality will further increase customer interest in using this service.